Manajemen Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Pendidikan di SMP Negeri 60 Palembang - Maleluan Pramana; Tri Widayatsih; Mahasir (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the principal's leadership management in improving the quality of education at SMP Negeri 60 Palembang. Data collection tools use interview methods, documentation, observation and literature review. Data analysis uses descriptive qualitative analysis with research stages referring to the theory of Miles and Huberman, namely collecting data, data reduction, data presentation, drawing conclusions. The results of the study stated that the leadership management of the head of the educational unit in improving the quality of education at SMP Negeri 60 Palembang has been implemented well through careful planning, organizing school resources, implementation and supervision carried out effectively. Some of the obstacles faced in efforts to improve the quality of learning and competence of teaching staff at SMP Negeri 60 Palembang lie in the aspect of improving the quality of learning and increasing the competence of teaching staff, including the lack of mastery of learning technology and teachers' way of teaching which tends to be monotonous in class, namely always using the lecture method. The solution to several obstacles faced by the principal is through coaching to improve the competence of educators through supervision activities and self-development activities carried out through training and workshop activities and training. Motivate teaching staff to continue their studies at a higher level.